g (x) = -3x+5 -3x= 5 x= -5/3
7x + 5 + 3x is [ 10x + 5 ].That's the same thing as [ 2 times (5x + 1) ] .
( 5 + 3x )
4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3
3x-5=3x+5 There is no solution.
g (x) = -3x+5 -3x= 5 x= -5/3
7x + 5 + 3x is [ 10x + 5 ].That's the same thing as [ 2 times (5x + 1) ] .
( 5 + 3x )
4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3
It is equivalent to: 3x+6+5 = 3x+11
3x-5=3x+5 There is no solution.
5(5x - 3) = 5(3x + 7)There is no need to distribute, simply divide both sides by five5x - 3 = 3x + 7subtract 3x from both sides2x - 3 = 7add 3 to both sides2x = 10divide both sides by 2x = 5
(3x+2)-(5+7x) = 3x+2-5-7x = -4x-3 3x+2 is -4x-3 times greater than 5+7x.
The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.
-4x + 5 + 3x + 6 = -x + 11
3x - 5 + 3x = 1x + 15 3x + 3x -1x = 15 + 5 5x = 20 5x/5 = 20/5 x = 4
(3x + 1)(x + 5)